The Pirabas Formation (Early Miocene from Brazil) and the Tropical Western Central Atlantic Subprovince - Socorro, Orangel Aguilera; Páes, Eduardo Tavares (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2012)
The Neogene Tropical Western Central Atlantic-South American faunal assemblage from the Pirabas Formation (Early Miocene) has specific and unique features, which distinguishes it from the rest of the Proto-Caribbean Subprovince in diversity, paleoceanographic condition and ecosystems. Principal component analysis (PCA) distinguished three groups of localities with similar faunas (Group A: Ilha de Fortaleza, Colônia Pedro Teixeira and Praia de Fortalezinha; Group B: Estação Agronômica, Ilha de Marajó, Turiacu, Baixo Parnaíba, Aricuru and Salinópolis; Group C: Capanema B-17 Mine) and five different depositional facies (surf zone, beach, lagoons, tidal channel and tidal delta), in agreement with previous geological studies showing heterogeneous paleoenvironments among the outcrops. These heterogeneous lithostratigraphic sequences suggest different members, and may be related to different ages along the Pirabas sequence. The Neogene Northwestern Atlantic Subprovince is erected to encompass this entire geographical area.